2004
DOI: 10.1111/j.1440-1754.2004.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral metabolism changes in epileptic children receiving valproic acid

Abstract: Long-term and high dose VPA therapy may cause osteopenia, primarily in younger epileptic children. These patients should be followed closely by BMD measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 20 publications
10
60
2
2
Order By: Relevance
“…AEDs increase catabolism of 25-hydroxyvitamin D by induction of the hepatic P-450 enzyme system, leading to relative hypocalcemia, increased levels of parathyroid hormone (PTH), and subsequent low BMD (Dent et al, 1970;Keck et al, 1982;Chung and Ahn, 1994). However, some studies have suggested a significant reduction in BMD with non-enzymeinducing AEDs (Oner et al, 2004;Petty et al, 2005). Other environmental and epidemiological parameters including age, sex, diet, and mobility may also affect mineral metabolism (Pack and Morrell, 2001), suggesting a multifactorial etiology.…”
Section: Introductionmentioning
confidence: 99%
“…AEDs increase catabolism of 25-hydroxyvitamin D by induction of the hepatic P-450 enzyme system, leading to relative hypocalcemia, increased levels of parathyroid hormone (PTH), and subsequent low BMD (Dent et al, 1970;Keck et al, 1982;Chung and Ahn, 1994). However, some studies have suggested a significant reduction in BMD with non-enzymeinducing AEDs (Oner et al, 2004;Petty et al, 2005). Other environmental and epidemiological parameters including age, sex, diet, and mobility may also affect mineral metabolism (Pack and Morrell, 2001), suggesting a multifactorial etiology.…”
Section: Introductionmentioning
confidence: 99%
“…These drugs alter the metabolism and cause osteopenia and osteomalacia by leading clearance of vitamin D (29). Anticonvulsant drugs cause changes in bone metabolism and calcium levels and these drugs may lead to a decrease in bone mass (39). In previous studies increased ALP activities were reported in serum and different tissues (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in serum levels of total alkaline phosphatase have been reported in several studies 28,35,37 . In two studies, the osteocalcin levels of the patient group were significantly higher than the control group 5,27,36 . Urine values of deoxypyridinoline showed no significant difference between epileptic and healthy children 27,38,39 .…”
Section: Parameters/ Groupsmentioning
confidence: 94%
“…Some studies found results suggesting that serum calcium concentrations may be significantly lower in patients receiving VPA 28,33,34 . In many studies, serum levels of intact parathyroid hormone were within the normal range 28,30,32,34,35,36 . Increases in serum levels of total alkaline phosphatase have been reported in several studies 28,35,37 .…”
Section: Parameters/ Groupsmentioning
confidence: 99%
See 1 more Smart Citation